Comprehensive behavioral phenotyping of ryanodine receptor type3 (RyR3) knockout mice: Decreased social contact duration in two social interaction tests - Matsuo, Naoki; Tanda, Koichi; Nakanishi, Kazuo; Yamasaki, Nobuyuki; Toyama, Keiko; Takao, Keizo; Takeshima, Hiroshi; Miyakawa, Tsuyoshi (Frontiers in Behavioral Neuroscience, 2009)
Dynamic regulation of the intracellular Ca2+ concentration is crucial for various neuronal functions such as synaptic transmission and plasticity, and gene expression. Ryanodine receptors (RyRs) are a family of intracellular calcium release channels that mediate calcium-induced calcium release (CICR) from the endoplasmic reticulum. Among the three RyR isoforms, RyR3 is preferentially expressed in the brain especially in the hippocampus and striatum. To investigate the behavioral effects of RyR3 deficiency, we subjected RyR3 knockout (RyR3-/-) mice to a battery of behavioral tests. RyR3-/- mice exhibited significantly decreased social contact duration in two different social interaction tests, where two mice can freely move and make contacts with each other. They also exhibited hyperactivity and mildly impaired prepulse inhibition and latent inhibition while they did not show significant abnormalities in motor function and working and reference memory tests. These results suggest that RyR3 has an important role in locomotor activity and social behavior.